Valley - McEwan, Stacey (McEwan, Stacey. Glacian trilogy, 2024)
""All things find a way back home." At the bottom of the Chasm, Dawsyn and her followers traipse through the darkness to find their long-awaited home. But there are whispers all around them and safety is never guaranteed. With her powers much depleted, and food supplies running low, will they even survive the journey? Above, the Queen and the new King of Glacia still bay for Dawsyn's blood, and they will not stop in their quest to destroy her. And with the help of someone Dawsyn thought her friend, they creep ever closer. Long-buried secrets will be revealed, hearts will be broken and a new day will dawn. Who will reign in this climactic conclusion to the epic Glacian Trilogy?" --